CENTRAL COMPOSITE DESIGN FOR OPTIMIZING EXTRACTION OF EGCG FROM GREEN TEA LEAF (CAMELLIA SINENSIS L.) - Setyawan, Eka Indra; Setyowati, Erna Prawita; Rohman, Abdul; Nugroho, Akhmad Kharis (International Journal of Applied Pharmaceutics, 2018)
Objective: This study was intended to optimize the extraction condition using central composite design. Methods: Central composite cesign with three independent variables, namely water temperature, brewing time, and brewing number were used to obtain the optimum extraction condition. Two dependent variables, namely yield of extraction and epigallocatechingallate level were used as a response parameter. Epigallocatechin gallate level was determined by using high-performance liquid chromatography method. Results: Extraction yield was varied from 0.30 g to 0.72 g. All variables, namely water temperature, brewing time, and brewing number were able to increase the extraction yield. Epigallocatechingallate level was varied from 190.23 mg/g to 301.74 mg/g. Water temperature, brewing time, and both interaction were able to increase the epigallocatechin gallate level in green tea extract. Conclusion: Optimum extraction condition was shown using hot water at a temperature of 95 Â°C for 20 min and two-times infusions. The condition obtained extraction yield and epigallocatechingallate of 0.70 g and 286.87 mg/g dry weight, respectively.